2007
DOI: 10.1097/phm.0b013e31806dd2c8
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ventilatory Assistance During Exercise for Patients with Kyphoscoliosis

Abstract: The goal was to determine whether noninvasive ventilatory assistance (NIV) could facilitate exercise performance and benefit physiologic parameters for eight hypercapnic kyphoscoliosis patients using a cycloergometer for 6-min periods at a constant power (20 W). The exercise protocols were performed in random order while breathing unaided (spontaneous breathing test or SBT) and also while receiving NIV (NIV test or NIVT). The NIV was pressure support (15 cm H2O) plus positive end expiratory pressure (PEEP) (4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…While ventilation was increased during exercise with NIV, exercise capacity did not improve, and the authors concluded that there was no role for NIV as an adjunct to exercise training in patients with scoliosis. In contrast, other studies have reported benefi t [4,22,23]. TSUBOI et al [22] studied seven patients with chest wall restriction secondary to tuberculosis sequelae during constant work rate.…”
Section: Nocturnal Ventilatory Support and Exercise Performancementioning
confidence: 84%
See 1 more Smart Citation
“…While ventilation was increased during exercise with NIV, exercise capacity did not improve, and the authors concluded that there was no role for NIV as an adjunct to exercise training in patients with scoliosis. In contrast, other studies have reported benefi t [4,22,23]. TSUBOI et al [22] studied seven patients with chest wall restriction secondary to tuberculosis sequelae during constant work rate.…”
Section: Nocturnal Ventilatory Support and Exercise Performancementioning
confidence: 84%
“…A signifi cant correlation between the increase in exercise endurance and the reduction in breathlessness during NIV was noted [4,22]. Using a similar randomised cross over design in eight patients with kyphoscoliosis, NIV was shown to alleviate hypoventilation associated with light cycling, while reducing dyspnoea and perceived effort [23]. However, as seen in patients with COPD the immediate response to NIV-assisted exercise was variable, with some patients greatly improving exercise duration while others were slightly impaired [4].…”
Section: Lower-limb Exercisementioning
confidence: 99%
“…Patients who did not use ventilation experienced more significant acidosis, hypoxia, hypercapnia and dyspnoea [15].…”
Section: Exercise Training and Respiratory Rehabilitationmentioning
confidence: 99%
“…Berman et al [19] have indicated that pregnancy exacerbates scoliosis due to mechanical stress and pregnancy hormones; hence, Wong et al [16] have suggested reassessment of the spinal curvature after delivery. Obstetric complications include gestation hypertension, preeclampsia, preterm delivery and a higher risk of C-section [15,16]. Chopra et al [17] have noticed that all delivered babies had good Apgar scores and any of the babies had congenital malformations.…”
Section: Pregnancy and Deliverymentioning
confidence: 99%
“…Nocturnal NIV has been suggested as an addition to diurnal pulmonary rehabilitation in COPD patients [122,123]. NIV has also been used as an aid to exercise in patients with a restrictive ventilatory pattern [124,125]. Discard all masks, circuits, filters and headsets immediately and safely after use according to routine infection control procedures…”
Section: Rehabilitationmentioning
confidence: 99%